Remote electrical neuromodulation (REN) wearable device for adolescents with migraine: a real-world study of high-frequency abortive treatment suggests preventive effects - Monteith, Teshamae S.; Stark-Inbar, Alit; Shmuely, Sharon; Harris, Dagan; Garas, Sandy; Ironi, Alon; Kalika, Paige; Irwin, Samantha L. (Frontiers in Pain Research, 2023)
Migraine is the most common disabling headache type in children and adolescents, manifesting as attacks of disabling head pain and associated symptoms, and causing significant disability especially in those with a high frequency of migraine attacks. However, there is a paucity of preventive treatment options to reduce the number of monthly attacks in adolescents. This study aims to evaluate preventive benefits from frequent acute use of the Remote Electrical Neuromodulation (REN) for the acute management of migraine in adolescents. REN is a nonpharmacological, prescribed, wearable device (Nerivio®), FDA-cleared for acute and/or preventive treatment of migraine with or without aura in patients 12 years of age or older. It is worn on the arm for 45-minute treatments and controlled by a smartphone-app. It allows disease monitoring, synchronizing effective and safe treatment with prospective pain assessment. Real-world data from all adolescents who used REN for the acute treatment of migraine in a manner resembling the REN migraine prevention guideline of every-other-day was analyzed. A reduction in mean migraine treatment days from the first to the third month of consecutive REN treatment was seen, in addition to consistent improvement in acute pain responses and functional disability. Thus, frequent use of the wearable REN device by adolescents for the acute treatment of migraine pain was shown to reduce the mean number of monthly treatment days in subsequent months, suggesting potential migraine preventive benefits of REN in this subpopulation, similar to those found in a dedicated prevention randomized-controlled trial in adults.